Dietary exposure to neonicotinoid insecticides and health risks in the Chinese general population through two consecutive total diet studies. (February 2020) - Chen, Dawei; Zhang, Yiping; Lv, Bing; Liu, Zhibin; Han, Jiajun; Li, Jingguang; Zhao, Yunfeng; Wu, Yongning
Highlights: First survey of neonic residues in total dietary samples consumed by Chinese adults. Health risks of chronic exposure to neonics were investigated for the Chinese population by a TDS. 10 neonics were analyzed in 528 composite dietary samples from two consecutive TDS. Dietary intake may be one of the major pathways for human exposure to neonics. Abstract: Neonicotinoid insecticides are ubiquitous in food and the environment due to their wide use. Growing evidence suggests the adverse effects of neonicotinoids in many species, including mammals. Some studies have reported the urinary concentrations of neonicotinoids in human biological monitoring, but the potential risks of neonicotinoids on human health based on long-term chronic exposure studies in any general population have been rarely tackled. In this study, the dietary exposure to neonicotinoids of the Chinese adult population was studied on the basis of composite dietary samples collected from the 5th (2009–2012) and 6th (2015–2018) Chinese total diet studies (TDS). Residue levels of ten neonicotinoids were determined in 528 composite dietary samples from 24 provinces in China. Most of the samples (53.3% and 70.5% in the 5th and 6th TDS, respectively) that we analyzed contained the multi-residue of neonicotinoids. Imidacloprid and acetamiprid were the most frequently detected neonicotinoids, and thiamethoxam and clothianidin were increasingly used and found in the 6th TDS. The estimated daily intake (EDI) for total neonicotinoids was calculated to evaluate health risk of the Chinese adult population based on a relative potency factor assessment method. The mean EDIs of total neonicotinoids in the 5th and 6th TDS respectively reached 598.95 and 710.38 ng/kg bw per day. Although the mean EDIs of total neonics in 6th TDS was relatively higher than that in 5th TDS, no statistical difference was observed (p > 0.05). Vegetables were the main source of dietary exposure, but exposure via cereals and beverages and water must also be addressed in China. Although the average exposure for total neonicotinoids was much lower than the current chronic reference dose (57 μg/kg bw per day), the dietary exposure risks of a general population for total neonicotinoids should not be overlooked due to the ubiquity of neonicotinoids in food and the environment.